2020
DOI: 10.1155/2020/2172781
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Associations of Thyroid Hormone Levels with the Risk of Atherosclerosis in Euthyroid Type 2 Diabetic Patients in Central China

Abstract: Background. Thyroid function is associated with the etiology and pathogenesis of type 2 diabetes (T2D) and potentially contributes to the development of the complications of T2D. The association of thyroid hormones with atherosclerosis in euthyroid T2D patients is not clear. Purpose. To investigate the association of thyroid hormone levels with the risk of developing atherosclerosis in euthyroid T2D patients in Central China. Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 26 publications
(38 reference statements)
1
14
0
Order By: Relevance
“…This discrepancy can be explained by the fact that the different definitions of macrovascular complications were used in above studies. That is, the macrovascular complications in the studies by Wang et al [ 38 ] and Hu et al [ 12 ] were defined as atherosclerosis from the aorta, coronary, basilar and carotid, while our current study mainly focused on carotid atherosclerotic lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This discrepancy can be explained by the fact that the different definitions of macrovascular complications were used in above studies. That is, the macrovascular complications in the studies by Wang et al [ 38 ] and Hu et al [ 12 ] were defined as atherosclerosis from the aorta, coronary, basilar and carotid, while our current study mainly focused on carotid atherosclerotic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies regarding the associations between FT3 levels and macrovascular complications in euthyroid patients with type 2 diabetes are quite few. Recently, a study by Wang et al [ 38 ] displayed that diabetic patients with low-normal FT3 level were more likely to suffer from macrovascular complications than those with mid-and-high normal FT3 level. Hu et al [ 12 ] also revealed that there was a remarkable relation between diabetic macrovascular complications and normal FT3 (OR = 0.534, 95% CI 0.358–0.796).…”
Section: Discussionmentioning
confidence: 99%
“…Since BMI could influence the association between thyroid hormones and diabetes complications, we calculated the stratum-specific ORs for normal or underweight patients (BMI<25) and overweight or obese patients (BMI≥25) to test the effect modification by BMI. Based on the correlations between HbA1c and the development of atherosclerosis in T2DM patients demonstrated in previous researches, 13 patients with normal HbA1c (<6.0%) were rarely encountered in our study (only 26 patients). Hence, we performed sensitivity analyses by excluding patients with normal HbA1c.…”
Section: Methodsmentioning
confidence: 71%
“…However, a case-control study conducted in China suggested that low-normal FT3 and FT4 levels contributed to a high prevalence of atherosclerosis after adjusting for covariates. 13 However, TSH and FT3 to FT4 ratio did not show any significant association with the development of atherosclerosis. Moreover, they analyzed the association of thyroid function with HbA1c and the association of HbA1c with the prevalence of atherosclerosis.…”
Section: Discussionmentioning
confidence: 86%
“…Lately, some scholars further explored the associations of FT3 Levels and macrovascular complications in type 2 diabetic patients with normal thyroid function [42,43]. Different from us, Wang et al [42] showed that diabetic patients with low-normal FT3 level were more likely to suffer from macrovascular complications than those with mid-and-high normal FT3 level. Hu et al [43] also revealed that there was a remarkable relationship between diabetic macrovascular complications and normal FT3 (OR = 0.534, 95% CI 0.358-0.796).…”
Section: Discussionmentioning
confidence: 99%